Aluminum alloy conductor material for high-conductivity cable
By electroless plating and magnesium coating on the refining agent of the aluminum alloy cable conductor material, and adding cerium elements, the problem of insufficient strength and durability of the aluminum alloy cable conductor material is solved, and higher tensile strength and conductivity are achieved.
Patent Information
- Application Number
- CN202411925626.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aluminum alloy cable conductor materials have insufficient strength and durability, which leads to prone to failure of the cable during use.
By pretreating the Al-5Ti-1B refiner, including electroless plating and magnesium layer coating, a dense fine crystal magnesium layer is formed, the bonding and wetting of the refiner with the aluminum matrix is improved, and cerium is added to further fill the grain boundary defects.
It significantly improves the tensile strength and durability of aluminum alloy conductor materials, reduces the failure rate of cables, and maintains a high conductivity.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable aluminum alloy conductors, and in particular to an aluminum alloy conductor material for high-conductivity cables. Background Art
[0002] Aluminum alloy cables have the characteristics of lightweight design, corrosion resistance and environmental sustainability, and have shown obvious advantages in the application of wires and cables. Although the conductivity of aluminum alloy cables is slightly lower than that of copper, it can still meet the needs of power transmission, and at the same current carrying capacity, the weight is only about half of that of copper cables. In addition, compared with copper core cables, aluminum alloy cables have excellent corrosion resistance and can operate continuously and stably in harsh environments, thereby reducing the frequency of cable maintenance and replacement. Better bending performance is also an advantage of aluminum alloy cables, which is more convenient to install, reducing installation costs and manpower requirements. More importantly, the price of aluminum alloy cables is lower than that of copper core cables, which will translate into obvious economic benefits when used on a large scale.
[0003] Aluminum alloy cable refers to a cable made by adding copper, iron, magnesium, zinc, silicon and other elements to electrical aluminum. It is manufactured through special roll forming and twisting processes and annealing treatments. Doping aluminum with certain alloying elements can improve the electrical conductivity and high thermal conductivity of the material to a certain extent, thereby improving the overall performance of the material. Specific doping elements and preparation processes can not only enhance the electrical conductivity and high temperature resistance of the cable, but also effectively solve the strength problem of pure aluminum. Compared with traditional copper core cables and pure aluminum cables, aluminum alloy cables have many unique performance advantages, which makes them widely used in many fields. Summary of the invention
[0004] To this end, the present invention provides an aluminum alloy conductor material for a high-conductivity cable, the preparation steps comprising:
[0005] (1) Screening the aluminum titanium boron refiner powder, collecting the screened powder, soaking the screened powder in acetone, soaking in an ultrasonic environment to remove oil for more than 10 minutes, then separating the solid and liquid, drying the solid phase at 80±5°C for more than 1 hour, soaking the dried solid phase in a dilute hydrochloric acid solution for 90 to 120 seconds, then separating the solid and liquid, washing the solid phase with deionized water for more than 3 times, and drying at 80±5°C for more than 1 hour to obtain a pretreated refiner powder;
[0006] (2) preparing an ethanol solution of palladium dichloride and a chemical plating solution; immersing the pretreatment refiner powder in the ethanol solution of palladium dichloride, stirring the solution for more than 20 minutes under an ultrasonic environment, and then separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying to obtain an activated powder; immersing the activated powder in the chemical plating solution, heating it to 40±5° C. in a water bath, and plating it for 60 to 80 minutes at a temperature preservation, and condensing and refluxing during the heat preservation process; after the plating is completed, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying it at 80±5° C. for more than 1 hour to obtain a coating powder;
[0007] (3) preparing an aqueous solution of magnesium chloride and a Grignard reagent; heating the aqueous solution of magnesium chloride to 60±5° C. in a water bath, then immersing the coating powder in the aqueous solution of magnesium chloride, stirring at a constant temperature of 60±5° C. for 20 to 30 min, separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, drying, and then immersing the dried solid phase in the Grignard reagent in a nitrogen atmosphere, stirring for 10 min after adding the materials to disperse evenly, and then adding sodium hydride under stirring, continuing to stir for more than 20 min after the addition is completed, then separating the solid from the liquid, washing the solid phase with acetone for more than 2 times, washing with deionized water for more than 2 times, and drying to obtain a coated powder;
[0008] (4) placing aluminum alloy powder in a crucible and heating it to melt it into a molten liquid, scraping off the surface scum, then cooling it to 720±5° C., adding aluminum-cerium master alloy and the coated powder into the molten liquid, blowing argon and stirring to degas and refine, casting at 710±3° C., hot-rolling the ingot into an aluminum alloy rod, and then drawing it into an aluminum alloy wire with a wire drawing machine, and annealing the aluminum alloy wire to obtain the aluminum alloy conductor material for the cable.
[0009] Furthermore, in the step (1), the aluminum-titanium-boron refining agent powder is Al-5Ti-1B refining agent, and the sieved powder is sieved powder passing through a 1500-2000 mesh sieve.
[0010] Furthermore, in the step (1), the mass percentage of the solute in the dilute hydrochloric acid solution is 2% to 3%, and the solvent is water.
[0011] Furthermore, in the step (2), in the ethanol solution of palladium dichloride, the concentration of palladium dichloride is 0.2-0.3 g / L, and the solvent is ethanol; the concentrations of the components in the chemical plating solution are: anhydrous nickel chloride is 18-20 g / L, malic acid is 1.4-1.6 g / L, trisodium citrate is 15-18 g / L, sodium dodecyl sulfate is 0.8-0.9 mg / L, adipic acid is 1.3-1.6 g / L, dimethylamine borane is 8-10 g / L, and the solvent is water.
[0012] Furthermore, in the step (2), the mass ratio of the pretreatment refiner powder soaked in the palladium dichloride ethanol solution is pretreatment refiner powder: palladium dichloride ethanol solution = 1:30-50; the mass ratio of the activation powder soaked in the chemical plating solution is activation powder: chemical plating solution = 1:80-100.
[0013] Furthermore, in the step (3), the concentration of magnesium chloride in the aqueous solution of magnesium chloride is 40-50 g / L, and the solvent is water; the preparation method of the Grignard reagent is: polishing a magnesium strip with sandpaper, then soaking it in a dilute hydrochloric acid solution with a solute mass fraction of 10% for 10-15 seconds to remove the oxide scale, cutting it into magnesium chips, and then placing it in a reaction bottle with a nitrogen protective atmosphere; adding a mixture of ethyl bromide and tetrahydrofuran to the reaction bottle, stirring in a nitrogen atmosphere after the addition is completed, heating in a water bath to 30±2° C. for insulation, then adding iodine, stirring at a constant temperature of 30±2° C. after the addition until the magnesium chips are completely dissolved, and continuing to stir in a nitrogen atmosphere for more than 1 hour after the magnesium chips are completely dissolved, to obtain the Grignard reagent.
[0014] Furthermore, in the step (3), the coating powder is immersed in the aqueous solution of magnesium chloride at a mass ratio of coating powder: aqueous solution of magnesium chloride = 1:50-100; the dried solid phase is immersed in the Grignard reagent, and then sodium hydride is added at a mass ratio of dried solid phase: Grignard reagent: sodium hydride = 1:200:10-15.
[0015] Furthermore, in step (4), the aluminum alloy powder is 8030 aluminum alloy, the weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the mass ratio of the aluminum-cerium master alloy and the coated powder added to the aluminum alloy powder melted in the crucible is aluminum-cerium master alloy: coated powder: aluminum alloy powder = 0.6-0.8:0.7-0.8:100.
[0016] Furthermore, in the step (4), the annealing temperature of the annealing treatment is 400-420° C., the holding time is 2-3 hours, and after the holding is completed, the annealing furnace is closed and cooled to room temperature along with the furnace.
[0017] The beneficial effect of the present invention is that the aluminum alloy conductor material prepared by the method of the present invention significantly improves the tensile strength of the aluminum alloy, improves the durability of the cable, and reduces the failure rate of the cable during use while maintaining the high electrical conductivity of the aluminum alloy. The present invention uses Al-5Ti-1B refiner to perform grain refinement process on the cast aluminum alloy, but it is found in the test that the untreated refiner is directly added to the aluminum alloy melt, and the strength of the cast aluminum alloy is poor. This is mainly due to the wettability of the refiner and the melt and the insufficient bonding force between the refiner and the aluminum matrix. Although the addition of the refiner reduces the grain size of the material, due to improper treatment of the refiner, holes and microcracks are easily formed in the interface area between the refiner and the aluminum matrix, thereby causing the overall strength of the material to be insufficient. Therefore, the present invention firstly processes the refiner, chemically plates a Ni-B layer on the surface of the refiner, and then replaces part of the nickel with magnesium with a magnesium chloride solution, and uses the replaced magnesium as a crystal nucleus site, and reduces the Grignard reagent to form a coated magnesium layer to obtain a dense fine-grained magnesium layer, so that the coating can be firmly combined with the refiner itself on the one hand, and on the other hand, the good compatibility of magnesium and aluminum is utilized to improve the bonding force and wettability of the refiner and the aluminum body, so that the material as a whole is more dense, defects and microcracks are significantly reduced, mechanical strength is significantly improved, and electrical conductivity can also be improved to a certain extent. In addition, by adding cerium element, rare earth cerium is more inclined to form a rare earth phase distributed along the grain boundary, further filling the defects between the two phases, and improving the density of the material, and the rare earth itself also has a certain effect of refining the aluminum alloy grains. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the embodiments.
[0019] Example 1
[0020] A high-conductivity aluminum alloy conductor material for cables, the preparation steps comprising:
[0021] (1) Passing Al-5Ti-1B fine powder through a 1500 mesh sieve, collecting the sieved powder, soaking the sieved powder in acetone, soaking and degreasing for 10 minutes under an ultrasonic environment, and then separating the solid and liquid, drying the solid phase at 80° C. for 1 hour, and soaking the dried solid phase in a dilute hydrochloric acid solution for 90 seconds, wherein the mass percentage of the solute in the dilute hydrochloric acid solution is 2%, and the solvent is water; then separating the solid and liquid, washing the solid phase with deionized water for 3 times, and drying at 80° C. for 1 hour, to obtain a pretreated fine powder;
[0022] (2) preparing an ethanol solution of palladium dichloride and preparing a chemical plating solution; in the ethanol solution of palladium dichloride, the concentration of palladium dichloride is 0.2 g / L, and the solvent is ethanol; the concentrations of the components in the chemical plating solution are: anhydrous nickel chloride is 18 g / L, malic acid is 1.4 g / L, trisodium citrate is 15 g / L, sodium dodecyl sulfate is 0.8 mg / L, adipic acid is 1.3 g / L, dimethylamine borane is 8 g / L, and the solvent is water; soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride, soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride The mass ratio of the pretreatment refiner powder: palladium dichloride ethanol solution is 1:30; the solution is stirred under an ultrasonic environment for 20 minutes, then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain an activated powder; the activated powder is immersed in the chemical plating solution, and the mass ratio of the activated powder immersed in the chemical plating solution is activated powder: chemical plating solution = 1:80; the water bath is heated to 40°C, and the plating is carried out for 60 minutes under insulation, and condensation reflux is carried out during the insulation process; after the plating is completed, the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain a coating powder;
[0023] (3) preparing an aqueous solution of magnesium chloride, wherein the concentration of magnesium chloride in the aqueous solution is 40 g / L and the solvent is water; preparing a Grignard reagent; the preparation method of the Grignard reagent is as follows: polishing a magnesium bar with sandpaper, then soaking it in a dilute hydrochloric acid solution with a solute mass fraction of 10% for 10 seconds to remove the oxide scale, cutting it into magnesium chips, and then placing it in a reaction bottle with a nitrogen atmosphere; adding a mixture of ethyl bromide and tetrahydrofuran to the reaction bottle, wherein the bromine in the mixture of ethyl bromide and tetrahydrofuran is 10%; The volume ratio of ethane and tetrahydrofuran is ethyl bromide: tetrahydrofuran = 10:4; the amount ratio of magnesium chips to the mixture of ethyl bromide and tetrahydrofuran in the reaction bottle is magnesium chips: mixture of ethyl bromide and tetrahydrofuran = 0.06g: 10mL; after the addition is completed, stir in a nitrogen atmosphere, heat to 30°C in a water bath for insulation, and then add iodine, the mass ratio of the amount of iodine added to the amount of magnesium chips added is magnesium chips: iodine = 0.06g: 0.01g, and stir at a constant temperature of 30°C after the addition until the magnesium chips are completely dissolved. After the magnesium chips are completely dissolved, stirring is continued in a nitrogen atmosphere for 1 hour to obtain the Grignard reagent; the magnesium chloride aqueous solution is heated to 60°C in a water bath for insulation, and then the coating powder is immersed in the magnesium chloride aqueous solution, and the mass ratio of the coating powder immersed in the magnesium chloride aqueous solution is coating powder: magnesium chloride aqueous solution = 1:50; 60°C constant temperature stirring for 20 minutes, solid-liquid separation, the solid phase is washed with deionized water 3 times, and dried at 80°C for 1 hour, and then the dried solid phase is immersed in the Grignard reagent in a nitrogen protective atmosphere, and stirred for 10 minutes after adding to disperse evenly, and then sodium hydride is added under stirring, and the dried solid phase is immersed in the Grignard reagent, and then the mass ratio of adding sodium hydride is the dried solid phase: Grignard reagent: sodium hydride = 1:200:10; After the addition is completed, stirring is continued for 20 minutes, and then solid-liquid separation is performed, the solid phase is washed with acetone twice, washed with deionized water twice, and dried at 80°C for 1 hour to obtain a coated powder;
[0024] (4) placing aluminum alloy powder (8030 aluminum alloy, the composition is shown in Table 1) in a crucible, heating and melting it into a melt, scraping off the surface scum, and then cooling it to 720° C., adding aluminum-cerium master alloy and the coated powder into the melt, wherein the weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the weight ratio of the aluminum-cerium master alloy and the coated powder added to the aluminum alloy powder melted in the crucible is aluminum-cerium master alloy: coated powder: aluminum alloy powder = 0.6:0. 7:100; argon blowing, stirring, degassing and refining, casting at 710°C, hot rolling the ingot into an aluminum alloy rod (diameter 9.5mm), rough rolling at 600°C, and finish rolling at 550°C; then drawing it into an aluminum alloy wire with a diameter of 2.55mm using a wire drawing machine, and the deformation amount is set to 92.8%; the aluminum alloy wire is annealed at an annealing temperature of 400°C and a holding time of 2h. After the holding is completed, the annealing furnace is closed and cooled to room temperature with the furnace; the aluminum alloy conductor material for the cable is obtained.
[0025] Example 2
[0026] A high-conductivity aluminum alloy conductor material for cables, the preparation steps comprising:
[0027] (1) Passing Al-5Ti-1B fine powder through a 1500 mesh sieve, collecting the sieved powder, soaking the sieved powder in acetone, soaking and degreasing for 10 minutes under an ultrasonic environment, and then separating the solid and liquid, drying the solid phase at 80° C. for 1 hour, and soaking the dried solid phase in a dilute hydrochloric acid solution for 90 seconds, wherein the mass percentage of the solute in the dilute hydrochloric acid solution is 2%, and the solvent is water; then separating the solid and liquid, washing the solid phase with deionized water for 3 times, and drying at 80° C. for 1 hour, to obtain a pretreated fine powder;
[0028] (2) preparing an ethanol solution of palladium dichloride and preparing a chemical plating solution; in the ethanol solution of palladium dichloride, the concentration of palladium dichloride is 0.2 g / L, and the solvent is ethanol; the concentrations of the components in the chemical plating solution are: anhydrous nickel chloride is 19 g / L, malic acid is 1.5 g / L, trisodium citrate is 16 g / L, sodium dodecyl sulfate is 0.8 mg / L, adipic acid is 1.4 g / L, dimethylamine borane is 9 g / L, and the solvent is water; soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride, soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride The mass ratio of the pretreatment refiner powder: palladium dichloride ethanol solution is 1:30; the solution is stirred under an ultrasonic environment for 20 minutes, then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain an activated powder; the activated powder is immersed in the chemical plating solution, and the mass ratio of the activated powder immersed in the chemical plating solution is activated powder: chemical plating solution = 1:80; the water bath is heated to 40°C, and the plating is carried out for 60 minutes under insulation, and condensation reflux is carried out during the insulation process; after the plating is completed, the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain a coating powder;
[0029] (3) preparing an aqueous solution of magnesium chloride, wherein the concentration of magnesium chloride in the aqueous solution is 45 g / L and the solvent is water; preparing a Grignard reagent; the preparation method of the Grignard reagent is as follows: polishing a magnesium bar with sandpaper, then soaking it in a dilute hydrochloric acid solution with a solute mass fraction of 10% for 10 seconds to remove the oxide scale, cutting it into magnesium chips, and then placing it in a reaction bottle with a nitrogen atmosphere; adding a mixture of ethyl bromide and tetrahydrofuran to the reaction bottle, wherein the bromine in the mixture of ethyl bromide and tetrahydrofuran is 10%; The volume ratio of ethane and tetrahydrofuran is ethyl bromide: tetrahydrofuran = 10:4; the amount ratio of magnesium chips to the mixture of ethyl bromide and tetrahydrofuran in the reaction bottle is magnesium chips: mixture of ethyl bromide and tetrahydrofuran = 0.06g: 10mL; after the addition is completed, stir in a nitrogen atmosphere, heat to 30°C in a water bath for insulation, and then add iodine, the mass ratio of the amount of iodine added to the amount of magnesium chips added is magnesium chips: iodine = 0.06g: 0.01g, and stir at a constant temperature of 30°C after the addition until the magnesium chips are completely dissolved. After the magnesium chips are completely dissolved, stirring is continued in a nitrogen atmosphere for 1 hour to obtain the Grignard reagent; the magnesium chloride aqueous solution is heated to 60°C in a water bath for insulation, and then the coating powder is immersed in the magnesium chloride aqueous solution, and the mass ratio of the coating powder immersed in the magnesium chloride aqueous solution is coating powder: magnesium chloride aqueous solution = 1:50; 60°C constant temperature stirring for 20 minutes, solid-liquid separation, the solid phase is washed with deionized water 3 times, and dried at 80°C for 1 hour, and then the dried solid phase is immersed in the Grignard reagent in a nitrogen protective atmosphere, and stirred for 10 minutes after adding to disperse evenly, and then sodium hydride is added under stirring, and the dried solid phase is immersed in the Grignard reagent, and then the mass ratio of adding sodium hydride is the dried solid phase: Grignard reagent: sodium hydride = 1:200:10; After the addition is completed, stirring is continued for 20 minutes, and then solid-liquid separation is performed, the solid phase is washed with acetone twice, washed with deionized water twice, and dried at 80°C for 1 hour to obtain a coated powder;
[0030] (4) placing aluminum alloy powder (8030 aluminum alloy, the composition is shown in Table 1) in a crucible, heating and melting it into a melt, scraping off the surface scum, and then cooling it to 720° C., adding aluminum-cerium master alloy and the coated powder into the melt, wherein the weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the weight ratio of the aluminum-cerium master alloy and the coated powder added to the aluminum alloy powder melted in the crucible is aluminum-cerium master alloy: coated powder: aluminum alloy powder = 0.7:0. 7:100; argon blowing, stirring, degassing and refining, casting at 710°C, hot rolling the ingot into an aluminum alloy rod (diameter 9.5mm), rough rolling at 600°C, and finish rolling at 550°C; then drawing it into an aluminum alloy wire with a diameter of 2.55mm using a wire drawing machine, and the deformation amount is set to 92.8%; the aluminum alloy wire is annealed at an annealing temperature of 400°C and a holding time of 2h. After the holding is completed, the annealing furnace is closed and cooled to room temperature with the furnace; the aluminum alloy conductor material for the cable is obtained.
[0031] Example 3
[0032] A high-conductivity aluminum alloy conductor material for cables, the preparation steps comprising:
[0033] (1) Passing Al-5Ti-1B fine powder through a 1500 mesh sieve, collecting the sieved powder, soaking the sieved powder in acetone, soaking and degreasing for 10 minutes under an ultrasonic environment, and then separating the solid and liquid, drying the solid phase at 80° C. for 1 hour, and soaking the dried solid phase in a dilute hydrochloric acid solution for 90 seconds, wherein the mass percentage of the solute in the dilute hydrochloric acid solution is 2%, and the solvent is water; then separating the solid and liquid, washing the solid phase with deionized water for 3 times, and drying at 80° C. for 1 hour, to obtain a pretreated fine powder;
[0034] (2) preparing an ethanol solution of palladium dichloride and preparing a chemical plating solution; in the ethanol solution of palladium dichloride, the concentration of palladium dichloride is 0.3 g / L, and the solvent is ethanol; the concentrations of the components in the chemical plating solution are: anhydrous nickel chloride is 19 g / L, malic acid is 1.5 g / L, trisodium citrate is 17 g / L, sodium dodecyl sulfate is 0.9 mg / L, adipic acid is 1.5 g / L, dimethylamine borane is 9 g / L, and the solvent is water; soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride, soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride The mass ratio of the pretreatment refiner powder: palladium dichloride ethanol solution is 1:30; the solution is stirred under an ultrasonic environment for 20 minutes, then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain an activated powder; the activated powder is immersed in the chemical plating solution, and the mass ratio of the activated powder immersed in the chemical plating solution is activated powder: chemical plating solution = 1:80; the water bath is heated to 40°C, and the plating is carried out for 60 minutes under insulation, and condensation reflux is carried out during the insulation process; after the plating is completed, the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain a coating powder;
[0035] (3) preparing an aqueous solution of magnesium chloride, wherein the concentration of magnesium chloride in the aqueous solution is 45 g / L and the solvent is water; preparing a Grignard reagent; the preparation method of the Grignard reagent is as follows: polishing a magnesium bar with sandpaper, then soaking it in a dilute hydrochloric acid solution with a solute mass fraction of 10% for 10 seconds to remove the oxide scale, cutting it into magnesium chips, and then placing it in a reaction bottle with a nitrogen atmosphere; adding a mixture of ethyl bromide and tetrahydrofuran to the reaction bottle, wherein the bromine in the mixture of ethyl bromide and tetrahydrofuran is 10%; The volume ratio of ethane and tetrahydrofuran is ethyl bromide: tetrahydrofuran = 10:4; the amount ratio of magnesium chips to the mixture of ethyl bromide and tetrahydrofuran in the reaction bottle is magnesium chips: mixture of ethyl bromide and tetrahydrofuran = 0.06g: 10mL; after the addition is completed, stir in a nitrogen atmosphere, heat to 30°C in a water bath for insulation, and then add iodine, the mass ratio of the amount of iodine added to the amount of magnesium chips added is magnesium chips: iodine = 0.06g: 0.01g, and stir at a constant temperature of 30°C after the addition until the magnesium chips are completely dissolved. After the magnesium chips are completely dissolved, stirring is continued for 1 hour in a nitrogen atmosphere to obtain the Grignard reagent; the magnesium chloride aqueous solution is heated to 60° C. in a water bath to keep warm, and then the coating powder is immersed in the magnesium chloride aqueous solution, and the mass ratio of the coating powder immersed in the magnesium chloride aqueous solution is coating powder: magnesium chloride aqueous solution = 1:50; stirring at 60° C. for 20 minutes, solid-liquid separation, the solid phase is washed 3 times with deionized water, and dried at 80° C. for 1 hour, and then the dried solid phase is immersed in the Grignard reagent in a nitrogen protective atmosphere, and stirred for 10 minutes after adding to disperse evenly, and then sodium hydride is added under stirring, and the dried solid phase is immersed in the Grignard reagent, and then the mass ratio of adding sodium hydride is the dried solid phase: Grignard reagent: sodium hydride = 1:200:15; stirring is continued for 20 minutes after the addition is completed, and then solid-liquid separation is performed, the solid phase is washed 2 times with acetone, 2 times with deionized water, and dried at 80° C. for 1 hour to obtain a coated powder;
[0036] (4) placing aluminum alloy powder (8030 aluminum alloy, the composition is shown in Table 1) in a crucible, heating and melting it into a melt, scraping off the surface scum, and then cooling it to 720° C., adding aluminum-cerium master alloy and the coated powder into the melt, wherein the weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the weight ratio of the aluminum-cerium master alloy and the coated powder added to the aluminum alloy powder melted in the crucible is aluminum-cerium master alloy: coated powder: aluminum alloy powder = 0.7:0. 8:100; argon blowing, stirring, degassing and refining, casting at 710°C, hot rolling the ingot into an aluminum alloy rod (diameter 9.5mm), rough rolling at 600°C, and finish rolling at 550°C; then drawing it into an aluminum alloy wire with a diameter of 2.55mm using a wire drawing machine, and the deformation amount is set to 92.8%; the aluminum alloy wire is annealed at an annealing temperature of 400°C and a holding time of 2h. After the holding is completed, the annealing furnace is closed and cooled to room temperature with the furnace; the aluminum alloy conductor material for the cable is obtained.
[0037] Example 4
[0038] A high-conductivity aluminum alloy conductor material for cables, the preparation steps comprising:
[0039] (1) Passing Al-5Ti-1B fine powder through a 1500 mesh sieve, collecting the sieved powder, soaking the sieved powder in acetone, soaking and degreasing for 10 minutes under an ultrasonic environment, and then separating the solid and liquid, drying the solid phase at 80° C. for 1 hour, and soaking the dried solid phase in a dilute hydrochloric acid solution for 90 seconds, wherein the mass percentage of the solute in the dilute hydrochloric acid solution is 2%, and the solvent is water; then separating the solid and liquid, washing the solid phase with deionized water for 3 times, and drying at 80° C. for 1 hour, to obtain a pretreated fine powder;
[0040] (2) preparing an ethanol solution of palladium dichloride and preparing a chemical plating solution; in the ethanol solution of palladium dichloride, the concentration of palladium dichloride is 0.3 g / L, and the solvent is ethanol; the concentrations of the components in the chemical plating solution are: anhydrous nickel chloride is 20 g / L, malic acid is 1.6 g / L, trisodium citrate is 18 g / L, sodium dodecyl sulfate is 0.9 mg / L, adipic acid is 1.6 g / L, dimethylamine borane is 10 g / L, and the solvent is water; soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride, soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride The mass ratio in the liquid is pretreatment refiner powder: palladium dichloride ethanol solution = 1:30; the solution is stirred under ultrasonic environment for 20 minutes, then solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain activated powder; the activated powder is immersed in the chemical plating solution, and the mass ratio of the activated powder immersed in the chemical plating solution is activated powder: chemical plating solution = 1:80; the water bath is heated to 40°C, and the plating is carried out for 60 minutes under insulation, and condensation reflux is carried out during the insulation process; after the plating is completed, the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain a coating powder;
[0041] (3) preparing an aqueous solution of magnesium chloride, wherein the concentration of magnesium chloride in the aqueous solution is 50 g / L and the solvent is water; preparing a Grignard reagent; the preparation method of the Grignard reagent is as follows: polishing a magnesium bar with sandpaper, then soaking it in a dilute hydrochloric acid solution with a solute mass fraction of 10% for 10 seconds to remove the oxide scale, cutting it into magnesium chips, and then placing it in a reaction bottle with a nitrogen atmosphere; adding a mixture of ethyl bromide and tetrahydrofuran to the reaction bottle, wherein the bromine in the mixture of ethyl bromide and tetrahydrofuran is 10%; The volume ratio of ethane and tetrahydrofuran is ethyl bromide: tetrahydrofuran = 10:4; the amount ratio of magnesium chips to the mixture of ethyl bromide and tetrahydrofuran in the reaction bottle is magnesium chips: mixture of ethyl bromide and tetrahydrofuran = 0.06g: 10mL; after the addition is completed, stir in a nitrogen atmosphere, heat to 30°C in a water bath for insulation, and then add iodine, the mass ratio of the amount of iodine added to the amount of magnesium chips added is magnesium chips: iodine = 0.06g: 0.01g, and stir at a constant temperature of 30°C after the addition until the magnesium chips are completely dissolved. After the magnesium chips are completely dissolved, stirring is continued for 1 hour in a nitrogen atmosphere to obtain the Grignard reagent; the magnesium chloride aqueous solution is heated to 60° C. in a water bath to keep warm, and then the coating powder is immersed in the magnesium chloride aqueous solution, and the mass ratio of the coating powder immersed in the magnesium chloride aqueous solution is coating powder: magnesium chloride aqueous solution = 1:50; stirring at 60° C. for 20 minutes, solid-liquid separation, the solid phase is washed 3 times with deionized water, and dried at 80° C. for 1 hour, and then the dried solid phase is immersed in the Grignard reagent in a nitrogen protective atmosphere, and stirred for 10 minutes after adding to disperse evenly, and then sodium hydride is added under stirring, and the dried solid phase is immersed in the Grignard reagent, and then the mass ratio of adding sodium hydride is the dried solid phase: Grignard reagent: sodium hydride = 1:200:15; stirring is continued for 20 minutes after the addition is completed, and then solid-liquid separation is performed, the solid phase is washed 2 times with acetone, 2 times with deionized water, and dried at 80° C. for 1 hour to obtain a coated powder;
[0042] (4) placing aluminum alloy powder (8030 aluminum alloy, the composition is shown in Table 1) in a crucible, heating and melting it into a melt, scraping off the surface scum, and then cooling it to 720° C., adding aluminum-cerium master alloy and the coated powder into the melt, wherein the weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the weight ratio of the aluminum-cerium master alloy and the coated powder added to the aluminum alloy powder melted in the crucible is aluminum-cerium master alloy: coated powder: aluminum alloy powder = 0.8:0. 8:100; argon blowing, stirring, degassing and refining, casting at 710°C, hot rolling the ingot into an aluminum alloy rod (diameter 9.5mm), rough rolling at 600°C, and finish rolling at 550°C; then drawing it into an aluminum alloy wire with a diameter of 2.55mm using a wire drawing machine, and the deformation amount is set to 92.8%; the aluminum alloy wire is annealed at an annealing temperature of 400°C and a holding time of 2h. After the holding is completed, the annealing furnace is closed and cooled to room temperature with the furnace; the aluminum alloy conductor material for the cable is obtained.
[0043] Comparative Example 1
[0044] An aluminum alloy conductor material for comparison, the preparation steps include:
[0045] (1) Passing Al-5Ti-1B fine powder through a 1500 mesh sieve, collecting the sieved powder, soaking the sieved powder in acetone, soaking and degreasing for 10 minutes under an ultrasonic environment, and then separating the solid and liquid, drying the solid phase at 80° C. for 1 hour, and soaking the dried solid phase in a dilute hydrochloric acid solution for 90 seconds, wherein the mass percentage of the solute in the dilute hydrochloric acid solution is 2%, and the solvent is water; then separating the solid and liquid, washing the solid phase with deionized water for 3 times, and drying at 80° C. for 1 hour, to obtain a pretreated fine powder;
[0046] (2) placing aluminum alloy powder (8030 aluminum alloy, the composition is shown in Table 1) in a crucible and heating it to melt it into a molten liquid, scraping off the scum on the surface, and then cooling it to 720° C., adding aluminum-cerium master alloy and the pretreatment refiner powder into the molten liquid, wherein the weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the weight ratio of the aluminum-cerium master alloy and the pretreatment refiner powder added to the aluminum alloy powder melted in the crucible is aluminum-cerium master alloy: pretreatment refiner powder: aluminum alloy powder = 0.7:0.8:100; argon blowing, stirring, degassing and refining, casting at 710°C, hot rolling the ingot into an aluminum alloy rod (diameter 9.5mm), rough rolling at 600°C, and finish rolling at 550°C; then drawing it into an aluminum alloy wire with a diameter of 2.55mm using a wire drawing machine, and the deformation amount is set to 92.8%; the aluminum alloy wire is annealed at an annealing temperature of 400°C and a holding time of 2h. After the holding is completed, the annealing furnace is closed and cooled to room temperature with the furnace; the aluminum alloy conductor material described in this comparative example is obtained.
[0047] Comparative Example 2
[0048] An aluminum alloy conductor material for comparison, the preparation steps include:
[0049] (1) Passing Al-5Ti-1B fine powder through a 1500 mesh sieve, collecting the sieved powder, soaking the sieved powder in acetone, soaking and degreasing for 10 minutes under an ultrasonic environment, and then separating the solid and liquid, drying the solid phase at 80° C. for 1 hour, and soaking the dried solid phase in a dilute hydrochloric acid solution for 90 seconds, wherein the mass percentage of the solute in the dilute hydrochloric acid solution is 2%, and the solvent is water; then separating the solid and liquid, washing the solid phase with deionized water for 3 times, and drying at 80° C. for 1 hour, to obtain a pretreated fine powder;
[0050] (2) preparing an aqueous solution of magnesium chloride, wherein the concentration of magnesium chloride in the aqueous solution is 45 g / L and the solvent is water; preparing a Grignard reagent; the preparation method of the Grignard reagent is as follows: polishing a magnesium bar with sandpaper, then soaking it in a dilute hydrochloric acid solution with a solute mass fraction of 10% for 10 seconds to remove the oxide scale, cutting it into magnesium chips, and then placing it in a reaction bottle with a nitrogen protective atmosphere; adding a mixture of ethyl bromide and tetrahydrofuran to the reaction bottle, wherein the ethyl bromide and tetrahydrofuran in the mixture are 10% by mass; The volume ratio of tetrahydrofuran mixture is ethyl bromide: tetrahydrofuran = 10:4; the amount ratio of magnesium chips to the mixture of ethyl bromide and tetrahydrofuran in the reaction bottle is magnesium chips: mixture of ethyl bromide and tetrahydrofuran = 0.06g: 10mL; after the addition is completed, stir in a nitrogen atmosphere, heat to 30°C in a water bath for insulation, and then add iodine, the mass ratio of the amount of iodine added to the amount of magnesium chips added is magnesium chips: iodine = 0.06g: 0.01g, and stir at a constant temperature of 30°C after the addition until the magnesium chips are completely dissolved. After dissolution, stirring is continued in a nitrogen atmosphere for 1 hour to obtain the Grignard reagent; the magnesium chloride aqueous solution is heated to 60° C. in a water bath to keep warm, and then the pretreatment refiner powder is immersed in the magnesium chloride aqueous solution, and the mass ratio of the pretreatment refiner powder immersed in the magnesium chloride aqueous solution is pretreatment refiner powder: magnesium chloride aqueous solution = 1:50; stirring at a constant temperature of 60° C. for 20 minutes, solid-liquid separation, the solid phase is washed with deionized water 3 times, and dried at 80° C. for 1 hour, and then the dried solid phase is immersed in the Grignard reagent in a nitrogen protective atmosphere, and stirred for 10 minutes after adding to disperse evenly, and then sodium hydride is added under stirring, and the dried solid phase is immersed in the Grignard reagent, and then the mass ratio of sodium hydride added is the dried solid phase: Grignard reagent: sodium hydride = 1:200:15; stirring is continued for 20 minutes after the addition is completed, and then solid-liquid separation is performed, the solid phase is washed with acetone twice, washed with deionized water twice, and dried at 80° C. for 1 hour to obtain a coated powder;
[0051] (3) Aluminum alloy powder (8030 aluminum alloy, the composition is shown in Table 1) is placed in a crucible and heated to melt into a molten liquid, the surface scum is scraped off, and then the temperature is lowered to 720° C., and aluminum-cerium master alloy and the coated powder are added to the molten liquid. The weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the weight ratio of the aluminum-cerium master alloy and the coated powder to the aluminum alloy powder placed in the crucible is aluminum-cerium master alloy: coated powder: aluminum alloy powder = 0.7:0. 8:100; argon blowing, stirring, degassing and refining, casting at 710°C, hot rolling the ingot into an aluminum alloy rod (diameter 9.5 mm), rough rolling at 600°C, and finish rolling at 550°C; then drawing it into an aluminum alloy wire with a diameter of 2.55 mm using a wire drawing machine, and the deformation amount is set to 92.8%; the aluminum alloy wire is annealed at an annealing temperature of 400°C and a holding time of 2h. After the holding is completed, the annealing furnace is closed and cooled to room temperature with the furnace; the aluminum alloy conductor material described in this comparative example is obtained.
[0052] Comparative Example 3
[0053] An aluminum alloy conductor material for comparison, the preparation steps include:
[0054] (1) Passing Al-5Ti-1B fine powder through a 1500 mesh sieve, collecting the sieved powder, soaking the sieved powder in acetone, soaking and degreasing for 10 minutes under an ultrasonic environment, and then separating the solid and liquid, drying the solid phase at 80° C. for 1 hour, and soaking the dried solid phase in a dilute hydrochloric acid solution for 90 seconds, wherein the mass percentage of the solute in the dilute hydrochloric acid solution is 2%, and the solvent is water; then separating the solid and liquid, washing the solid phase with deionized water for 3 times, and drying at 80° C. for 1 hour, to obtain a pretreated fine powder;
[0055] (2) preparing an ethanol solution of palladium dichloride and preparing a chemical plating solution; in the ethanol solution of palladium dichloride, the concentration of palladium dichloride is 0.3 g / L, and the solvent is ethanol; the concentrations of the components in the chemical plating solution are: anhydrous nickel chloride is 19 g / L, malic acid is 1.5 g / L, trisodium citrate is 17 g / L, sodium dodecyl sulfate is 0.9 mg / L, adipic acid is 1.5 g / L, dimethylamine borane is 9 g / L, and the solvent is water; soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride, soaking the pretreatment refiner powder in the ethanol solution of palladium dichloride The mass ratio of the pretreatment refiner powder: palladium dichloride ethanol solution is 1:30; the solution is stirred under an ultrasonic environment for 20 minutes, then the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain an activated powder; the activated powder is immersed in the chemical plating solution, and the mass ratio of the activated powder immersed in the chemical plating solution is activated powder: chemical plating solution = 1:80; the water bath is heated to 40°C, and the plating is carried out for 60 minutes under insulation, and condensation reflux is carried out during the insulation process; after the plating is completed, the solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 80°C for 1 hour to obtain a coating powder;
[0056] (3) preparing an aqueous solution of magnesium chloride, wherein the concentration of magnesium chloride in the aqueous solution of magnesium chloride is 45 g / L, and the solvent is water; heating the aqueous solution of magnesium chloride to 60° C. in a water bath and then immersing the coating powder in the aqueous solution of magnesium chloride, wherein the mass ratio of the coating powder to the aqueous solution of magnesium chloride is 1:50; stirring at a constant temperature of 60° C. for 20 min, separating the solid and the liquid, washing the solid phase with deionized water for 3 times, and drying at 80° C. for 1 h to obtain the coated powder of this comparative example;
[0057] (4) placing aluminum alloy powder (8030 aluminum alloy, the composition is shown in Table 1) in a crucible, heating and melting it into a melt, scraping off the surface scum, and then cooling it to 720° C., adding aluminum-cerium master alloy and the coated powder into the melt, wherein the weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the weight ratio of the aluminum-cerium master alloy and the coated powder added to the aluminum alloy powder melted in the crucible is aluminum-cerium master alloy: coated powder: aluminum alloy powder = 0.7:0. 8:100; argon blowing, stirring, degassing and refining, casting at 710°C, hot rolling the ingot into an aluminum alloy rod (diameter 9.5 mm), rough rolling at 600°C, and finish rolling at 550°C; then drawing it into an aluminum alloy wire with a diameter of 2.55 mm using a wire drawing machine, and the deformation amount is set to 92.8%; the aluminum alloy wire is annealed at an annealing temperature of 400°C and a holding time of 2h. After the holding is completed, the annealing furnace is closed and cooled to room temperature with the furnace; the aluminum alloy conductor material described in this comparative example is obtained.
[0058] Example 5
[0059] The tensile strength of the aluminum alloy conductor material prepared by the methods described in the above embodiments and comparative examples was tested on a universal testing machine, and the tensile rate was set to 2 mm / min. The conductivity of the aluminum alloy rod (diameter 9.5 mm) prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of standard GB / T12966-2008, and the test samples were processed into discs with a diameter of 9.5 mm and a thickness of 3 mm. Three samples were tested in each group, and the average value was taken as the conductivity value of the group. The results are shown in Table 2.
[0060] As shown in Table 2, the aluminum alloy conductor material prepared by the method of the present invention significantly improves the tensile strength of the aluminum alloy, improves the durability of the cable, and reduces the failure rate of the cable during use while maintaining the high electrical conductivity of the aluminum alloy. The present invention performs a grain refining process on the cast aluminum alloy by using an Al-5Ti-1B refiner, but it is found during the test that the untreated refiner is directly added to the aluminum alloy melt, and the strength of the cast aluminum alloy is poor. This is mainly due to the wettability of the refiner and the melt and the insufficient bonding force between the refiner and the aluminum matrix. Although the addition of the refiner reduces the grain size of the material, due to improper treatment of the refiner, holes and microcracks are easily formed in the interface area between the refiner and the aluminum matrix, thereby causing insufficient strength of the material as a whole. Therefore, the present invention firstly processes the refiner, chemically plates a Ni-B layer on the surface of the refiner, and then replaces part of the nickel with magnesium with a magnesium chloride solution, and uses the replaced magnesium as a crystal nucleus site, and reduces the Grignard reagent to form a coated magnesium layer to obtain a dense fine-grained magnesium layer, so that the coating can be firmly combined with the refiner itself on the one hand, and on the other hand, the good compatibility of magnesium and aluminum is utilized to improve the bonding force and wettability of the refiner and the aluminum body, so that the material as a whole is more dense, defects and microcracks are significantly reduced, mechanical strength is significantly improved, and electrical conductivity can also be improved to a certain extent. In addition, by adding cerium element, rare earth cerium is more inclined to form a rare earth phase distributed along the grain boundary, further filling the defects between the two phases, and improving the density of the material, and the rare earth itself also has a certain effect of refining the aluminum alloy grains.
[0061] Table 1
[0062] Element Si Fe Cu Mg Zn B Al Content wt% 0.056 0.431 0.228 0.015 0.033 0.006 margin
[0063] Table 2
[0064] Experimental Group Tensile strength(MPa) Conductivity (%IACS) Example 1 138 61.47 Example 2 143 61.52 Example 3 146 61.53 Example 4 145 61.50 Comparative Example 1 109 60.08 Comparative Example 2 126 60.64 Comparative Example 3 122 60.39
[0065] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. An aluminum alloy conductor material for a high conductivity cable, characterized in that: The preparation steps include: (1) Screening the aluminum titanium boron refiner powder, collecting the screened powder, soaking the screened powder in acetone, soaking in an ultrasonic environment to remove oil for more than 10 minutes, then separating the solid and liquid, drying the solid phase at 80±5°C for more than 1 hour, soaking the dried solid phase in a dilute hydrochloric acid solution for 90 to 120 seconds, then separating the solid and liquid, washing the solid phase with deionized water for more than 3 times, and drying at 80±5°C for more than 1 hour to obtain a pretreated refiner powder; (2) preparing an ethanol solution of palladium dichloride and a chemical plating solution; immersing the pretreatment refiner powder in the ethanol solution of palladium dichloride, stirring the solution for more than 20 minutes under an ultrasonic environment, and then separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying to obtain an activated powder; immersing the activated powder in the chemical plating solution, heating it to 40±5° C. in a water bath, and plating it for 60 to 80 minutes at a temperature preservation, and condensing and refluxing during the heat preservation process; after the plating is completed, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying it at 80±5° C. for more than 1 hour to obtain a coating powder; (3) preparing an aqueous solution of magnesium chloride and a Grignard reagent; heating the aqueous solution of magnesium chloride to 60±5° C. in a water bath, then immersing the coating powder in the aqueous solution of magnesium chloride, stirring at a constant temperature of 60±5° C. for 20 to 30 min, separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, drying, and then immersing the dried solid phase in the Grignard reagent in a nitrogen atmosphere, stirring for 10 min after adding the materials to disperse evenly, and then adding sodium hydride under stirring, continuing to stir for more than 20 min after the addition is completed, then separating the solid from the liquid, washing the solid phase with acetone for more than 2 times, washing with deionized water for more than 2 times, and drying to obtain a coated powder; (4) placing aluminum alloy powder in a crucible and heating it to melt it into a molten liquid, scraping off the surface scum, then cooling it to 720±5° C., adding aluminum-cerium master alloy and the coated powder into the molten liquid, blowing argon and stirring to degas and refine, casting at 710±3° C., hot-rolling the ingot into an aluminum alloy rod, and then drawing it into an aluminum alloy wire with a wire drawing machine, and annealing the aluminum alloy wire to obtain the aluminum alloy conductor material for the cable.
2. The aluminum alloy conductor material for high conductivity cable according to claim 1, characterized in that: In the step (1), the aluminum-titanium-boron refining agent powder is Al-5Ti-1B refining agent, and the sieved powder is sieved powder passing through a 1500-2000 mesh sieve.
3. The aluminum alloy conductor material for high conductivity cable according to claim 1, characterized in that: In the step (1), the mass percentage of the solute in the dilute hydrochloric acid solution is 2% to 3%, and the solvent is water.
4. The aluminum alloy conductor material for high conductivity cable according to claim 1, characterized in that: In the step (2), the concentration of palladium dichloride in the ethanol solution of palladium dichloride is 0.2-0.3 g / L, and the solvent is ethanol; the concentrations of the components in the chemical plating solution are: anhydrous nickel chloride is 18-20 g / L, malic acid is 1.4-1.6 g / L, trisodium citrate is 15-18 g / L, sodium dodecyl sulfate is 0.8-0.9 mg / L, adipic acid is 1.3-1.6 g / L, dimethylamine borane is 8-10 g / L, and the solvent is water.
5. The aluminum alloy conductor material for high conductivity cable according to claim 4, characterized in that: In the step (2), the mass ratio of the pretreatment refiner powder soaked in the palladium dichloride ethanol solution is pretreatment refiner powder: palladium dichloride ethanol solution = 1:30-50; the mass ratio of the activation powder soaked in the chemical plating solution is activation powder: chemical plating solution = 1:80-100.
6. The aluminum alloy conductor material for high conductivity cable according to claim 1, characterized in that: In the step (3), the concentration of magnesium chloride in the aqueous solution of magnesium chloride is 40-50 g / L, and the solvent is water. The preparation method of the Grignard reagent is as follows: a magnesium strip is polished with sandpaper, and then immersed in a dilute hydrochloric acid solution with a solute mass fraction of 10% for 10-15 seconds to remove the oxide scale, cut into magnesium chips, and then placed in a reaction bottle with a nitrogen protective atmosphere; a mixture of ethyl bromide and tetrahydrofuran is added to the reaction bottle, and after the addition is completed, the mixture is stirred in a nitrogen atmosphere, heated in a water bath to 30±2° C. for insulation, and then iodine is added. After the addition, the mixture is stirred at a constant temperature of 30±2° C. until the magnesium chips are completely dissolved, and after the magnesium chips are completely dissolved, the mixture is stirred in a nitrogen atmosphere for more than 1 hour to obtain the Grignard reagent.
7. The aluminum alloy conductor material for high conductivity cable according to claim 6, characterized in that: In the step (3), the coating powder is immersed in the aqueous solution of magnesium chloride in a mass ratio of coating powder: aqueous solution of magnesium chloride = 1:50-100; the dried solid phase is immersed in the Grignard reagent, and then sodium hydride is added in a mass ratio of dried solid phase: Grignard reagent: sodium hydride = 1:200:10-15.
8. The aluminum alloy conductor material for high conductivity cable according to claim 1, characterized in that: In the step (4), the aluminum alloy powder is 8030 aluminum alloy, the weight percentage of cerium in the aluminum-cerium master alloy is 10%, and the mass ratio of the aluminum-cerium master alloy and the coated powder added to the aluminum alloy powder melted in the crucible is aluminum-cerium master alloy: coated powder: aluminum alloy powder = 0.6-0.8:0.7-0.8:
100.
9. The aluminum alloy conductor material for high conductivity cable according to claim 1, characterized in that: In the step (4), the annealing temperature of the annealing treatment is 400-420° C., and the insulation time is 2-3 hours. After the insulation is completed, the annealing furnace is closed and cooled to room temperature along with the furnace.